2021
DOI: 10.46328/ijemst.2244
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Blended Project-based Learning Model and Creative Thinking Ability on Engineering Students' Learning Outcomes

Abstract: This research examines the effect of the blended project-based learning (PjBL) model and creative thinking ability on engineering students' drawing learning outcomes. Using a pre and post-test quasi-experimental design, the research included a sample of 80 students from two different classes at the Faculty of Engineering, UNIMED, North Sumatra, Indonesia. The data were analyzed using descriptive and inferential statistics through two-way ANOVA. Subsequently, the results showed that the members of experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 37 publications
1
53
0
6
Order By: Relevance
“…The learning process is essentially a pedagogical interaction between teachers, students, materials, and their environment (Arni & Indrayana, 2021). Mursid, Saragih, and Hartono (2022) explain that learning is a thought process. Knowledge does not come from the outside but is formed by the individual in a cognitive structure.…”
Section: Discussionmentioning
confidence: 99%
“…The learning process is essentially a pedagogical interaction between teachers, students, materials, and their environment (Arni & Indrayana, 2021). Mursid, Saragih, and Hartono (2022) explain that learning is a thought process. Knowledge does not come from the outside but is formed by the individual in a cognitive structure.…”
Section: Discussionmentioning
confidence: 99%
“…These results show an interaction between the effect of the PjBL model and creative thinking ability on the learning outcomes of engineering students. Therefore, lecturers need to use a blended PjBL model to ensure improved outcomes, alongside enhancing students' creative thinking abilities to increase the model's effectiveness [16].…”
Section: Resultsmentioning
confidence: 99%
“…Developing the ability to extend the problem has a strong creative component. Mursid et al (2022) realized a study that examined the effect of the blended project-based learning (PjBL) model and creative thinking ability on engineering students drawing learning outcomes. The results showed that the members of an experimental group, comprising students who participated in the blended PjBL model, obtained the highest engineering drawing learning outcomes.…”
Section: Discussionmentioning
confidence: 99%